2008
DOI: 10.1002/ajh.21156
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus in polycythemia vera is associated with a lower risk of arterial thrombosis

Abstract: Among 418 patients with polycythemia vera seen at our institution and in whom pruritus history was recorded, the presence of pruritus at diagnosis was documented in 131 (31%) and its absence in 287 (69%). Pruritus was less frequently reported by smokers (12% vs. 24%; P 5 0.004) and diabetics (5% vs. 11%; P 5 0.04). The presence of pruritus was associated with a lower rate of arterial thrombosis, both at diagnosis (8% vs. 17%; P 5 0.01) and during follow-up (16% vs. 30%; P 5 0.003). Multivariable analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…On the other hand, these patients also significantly more often suffer from gout, erythromelalgia, splenomegaly and central nervous vascular complications, so that the quantitative contribution of AP on total quality of life cannot be precisely determined. In contrast, other authors have observed a lower rate of arterial thrombosis in patients with AP [10]. AP patients also report a higher incidence of fatigue and pain which most probably correlates with further disease progression.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, these patients also significantly more often suffer from gout, erythromelalgia, splenomegaly and central nervous vascular complications, so that the quantitative contribution of AP on total quality of life cannot be precisely determined. In contrast, other authors have observed a lower rate of arterial thrombosis in patients with AP [10]. AP patients also report a higher incidence of fatigue and pain which most probably correlates with further disease progression.…”
Section: Discussionmentioning
confidence: 64%
“…In another patient with PV-associated pruritus who underwent skin biopsy before and after warm water contact, there was an increased number of mononuclear cells in the papillary dermis and epidermis, especially after water exposure [18]. A recent paper showed that the mast cells in patients with MPN were involved in the malignant process, and were 59 (range 21-89) [9] 29AE4 (females), 34AE5 (males) [7] >60 [16] Sex distribution Nearly equal [9] Nearly equal [16] F:M ratio 3 : 1 [16] Family history NA 33% [7] None [16] Relationship of pruritus to water contact…”
Section: Pathology Of Pv-associated Pruritusmentioning
confidence: 99%
“…Itching usually follows contact with water at any temperature, but less frequently after contact with cold water [17] In 50%, itching occurs during bath, hot water causes symptoms in 30% and cold water in 35% [7] Itching is invariably absent during bath, but starts soon after (during drying) [16] Clinical features Occurs in 42% of patients with PV, distributed over torso and extensor surface of limbs [10], lower rate of arterial thrombosis [9], negative impact on quality of life Onset of itching is upon contact with water, duration averages 40 min [7], condition is usually unremitting, psychiatric symptoms may be present [16] Fair colour, dry scaly skin (senile xerosis), females have more severe symptoms, itching begins in lower extremities and spreads upwards, but spares head, longer baths cause more severe itching, symptoms are worse in winter, progressive increase in symptoms [16] Histopathological features…”
Section: Pathology Of Pv-associated Pruritusmentioning
confidence: 99%
“…Although Ph Ϫ MPDs are recognized as clonal hematopoietic stem cell disorders frequently associated with a JAK2 mutation (JAK2V617F), the pathophysiology of the MPD-associated pruritus remains unclear. 12,15,16 We have recently shown that MCs were involved by the malignant process in patients with Ph Ϫ MPDs. 17 In the present study, we explored the hypothesis that MCs play an important role in pruritogenesis in Ph Ϫ MPDs.…”
Section: Introductionmentioning
confidence: 99%